Persepsi Review Produk Make Up Melalui Beauty di Vlogger Youtube - Nur Maghfirah Aesthetika; Nur Tita Kusdiyanti (Kanal: Jurnal Ilmu Komunikasi, 2020)
Youtube is a very popular media by the people in Indonesia, especially the makeup artist. According to data from Wearesocial, Youtube has occupied the first position with a percentage of approximately 88%, and then followed by a second position and so on by Facebook, Whatsapp, and Instagram. Yotube itself is about entertainment, Video clips, or Vlog (Video Blog) where the vlogs can contain about private vacation videos, promote goods or products, or daily activities in this research using video blogs From Tasya Farasya entitled "Focallure One Brand Makeup Tutorial!!". The purpose of this research is to find out how the perception of Make up artist (MUA) is a product review through beauty vlogger on Youtube. This research uses qualitative descriptive research method with in-depth interview techniques and participants in this study as many as 5 people in the Make up artist (MUA). The results of this research show that the informant budgeted that the video blog of Tasya Farasya which contained about the product review is beneficial and very helpful in product selection.